Canopy Microclimate and Leaf Traits Shape Interspecies Variation in Photosynthetic Temperature Responses of Evergreen Tropical Trees in the Congo Basin - Thomas Sibret; Félicien Meunier; Kristine Y. Crous; Sarah Lamotte; Marc Peaucelle; Louise Terryn; Pieter De Frenne; Ivan Janssens; Bernard Bonyoma; Hans Verbeeck; Marijn Bauters; Pascal Boeckx (Global Change Biology, 2026)
Tropical forests contribute disproportionately to global carbon cycling, yet their resilience under climate warming remains uncertain, partly due to limited understanding of leaf‐level temperature responses of photosynthesis. In particular, the role of fine‐scale canopy microclimate in shaping photosynthetic temperature responses in tropical trees has been overlooked. We quantified vertical microclimate variation and measured leaf‐level photosynthetic temperature responses in 13 coexisting evergreen tree species spanning the full canopy profile in a lowland Congo Basin forest. Leaf gas exchange measurements were integrated with structural leaf traits and high‐resolution microclimate profiles to assess how temperature conditions and ecological strategies shape photosynthetic responses. Photosynthetic traits, including the light‐saturated photosynthetic rate at the temperature optimum and stomatal conductance at the temperature optimum, increased with canopy height, with pioneer species showing steeper increases than non‐pioneers. The temperature optimum of photosynthesis ( T opt ) was positively related to both mean and maximum leaf temperature ( T leaf ), driven mainly by interspecific differences rather than intraspecific plasticity. This suggests that T opt reflects species‐level adaptation to the temperature conditions of their canopy niche rather than leaf‐level adjustment to local microclimate. Stomatal conductance influenced T leaf via transpiration and thereby contributed to shaping T opt . Leaves experiencing larger temperature fluctuations showed reduced sensitivity, reflected in a broader photosynthetic temperature‐response width ( Ω ). Ω was also positively associated with structural traits such as leaf mass per area and leaf dry matter content, both within and among species, indicating that greater structural investment helps sustain higher photosynthetic rates across wider temperature ranges and enhances tolerance to temperature variability. By linking canopy microclimate, physiological traits, and structural characteristics, our findings demonstrate how vertical microclimatic gradients and functional diversity jointly determine photosynthetic temperature responses in tropical forest trees. Incorporating leaf‐level temperature regimes, stomatal regulation, and trait variation into vegetation models could improve predictions of tropical forest carbon dynamics under climate change.